(untitled) (Journal of Economic Research & Business Administration, 2021)
Digital Kazakhstan programs are aimed at accelerating the pace of economic development of the Republic of Kazakhstan and improving the quality of life of the population through the use of digital technologies. The article is devoted to one of the most important areas of digitalization of the economy – the creation of robotic systems for managing the activities of firms, organizations and companies. Currently, robotics and robotic means are being introduced into various spheres of human activity and, in particular, in the economy. The most effective robotization can be used in control systems of manufacturing enterprises, firms, organizations through the use of robot-managers. The article describes the functions and tasks performed by robot managers that ensure the adaptation of firms to digital transformation, characterized by the use of broadband Internet, cloud services, RFID technologies, ERP systems, as well as the involvement of firms and companies in e-commerce. The structure and functional characteristics of robotic managers designed to control production processes are presented.The main structural elements included in the structure of robot managers are considered. The use of robot managers to manage the activities of firms and companies will help to improve the quality of management functions, improve management efficiency, which will lead to an increase in the return of investments, competitiveness and profitability of these enterprises. The robotization of our economy can become a locomotive for the overall economic growth of Kazakhstan in the near future. Key words: economy, digitalization, management, digital technologies, robotic systems, robot managers.